ISLAMIC CREDIT CARD PRODUCT DEVELOPMENT STRATEGY (CASE STUDY OF SHARIA BANKS IN INDONESIA) - Rafika Rahmawati; Agung Dharmawan Buchdadi; Adam Zakaria (FORPIM PTKIS ZONA TAPAL KUDA, 2026)
This research will map the internal and external factors that influence the development of Islamic Credit Card products in Indonesia and analyze the appropriate alternative strategies for the development of these products. The analysis was carried out, namely Internal Factors Evaluation (IFE) and External Factors Evaluation (EFE) matrix analysis, Internal and External (IE) matrix analysis, and SWOT analysis to determine strategic alternatives. The results of the IFE and EFE assessments identified that the development of Islamic credit cards in Indonesia is in quadrant IV, namely